Perbandingan Metode Simple Additive Weighting (SAW) dan Weight Product (WP) dalam Menentukan Penerima Zakat - Rayendra, Rayendra (Journal of Information System Research (JOSH), 2024)
Zakat is part of a person's assets, which according to Islam, if the assets exceed the nishab limit, the owner is obliged to hand them over to someone who has the right to receive them under certain conditions or is called mustahiq zakat. To determine zakat mustahiq, BAZNAS Solok City collects data on prospective zakat recipients and determines mustahiq based on criteria determined manually. Therefore, through this research, the Simple Additive Weighting (SAW) and Weighted Product (WP) methods are used to determine mustahiq zakat so that it can help BAZNAS Solok City in making decisions. There are five criteria used, residence status, monthly income, employment status, number of dependents, and monthly expenses. Monthly income is a cost criterion and the other is a profit criterion. After carrying out calculations using both methods, ranking results were obtained from prospective zakat recipients (mustahiq). In the SAW Method, the first ranking results were obtained for the fourth (A4) and ninth (A9) recipient candidates, as well as in the WP Method. However, there is a difference in ranking between third and fourth. It can be seen that the SAW and WP methods provide almost the same ranking results, but there are differences in several ranking orders even though the best rankings are in the same alternative. Through the sensitivity test, the results were obtained that the WP method has a higher sensitivity than the SAW method, that is 4,14% > 3,17%, so it can be concluded that the WP method is better used as decision support by decision makers, is BAZNAS Solok City.